Clavicular Hook Plate Removal: A Necessity or A Myth? Clavicular Hook Plate Removal - Rashid, Uzair; Wali, Abdulah; Ilyas, Saad; Ahmed, Ijaz; Rafiq, Humera; Rashid, Arsala (Pakistan Journal of Health Sciences, 2025)
Timely fixation of fractures of the clavicle or acromioclavicular joint dislocation is rising in popularity vs conservative management. This is primarily due to potential complications, such as impingement, which may result in chronic pain and limited shoulder mobility. Objectives: To find the cause and number of hardware removals among clavicular fractures. To assess whether clavicular plates caused any after effects when they were left in. Methods: A Total of 156 patients treated by hook plate for either fracture of distal clavicular fracture or treatment of acromioclavicular joint dislocation were enrolled from January 2024 to April 2024 in the Orthopedic Department of Gurki Trust Teaching Hospital. All patients were followed for 12 months postoperatively. Clinical results were gauged using different scores. Results: There were 107 male and 49 female. At follow up patients in group I were n=50 (64.5%), while group II had only n=15 (19.2%) patients who underwent hook plate removal. The pain VAS scale had a significant p-value of 0.0035 among both groups. The SST score was statistically significant with a p-value of 0.0026. On the last follow-up visit, the mean VAS, SST, and Constant-Murley scores had insignificant p-values, respectively, in both groups. Conclusions: Clavicular fracture or acromioclavicular joint dislocation fixation by using hook plates is a safe and reliable mode of treatment. Patients operated with hook plates for distal clavicular fractures are more comfortable, while those treated for acromioclavicular joint dislocation are keener for its removal.